Strategi Ekspor Indonesia dalam Menghadapi Perdagangan Bebas di Negara-Negara ASEAN - Arzella Zalzabyella; Nabilla Zahra; Mohammad Zein Saleh (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The ASEAN Economic Community (AEC) was formed with the aim to strengthen economic integration and reduce trade barriers, providing opportunities for member countries, including Indonesia, to improve their competitiveness in the international market, as globalization has driven economic growth and trade between countries, including in Southeast Asia. Indonesia has plenty of natural resources and a large population, which makes it have a lot of export potential, especially in the agricultural sector. However, facing issues such as inadequate infrastructure and fierce competition in the ASEAN market requires a strong export strategy. To beat the competition, Indonesia should concentrate on improving product quality, market access, human resource development, and the use of digital technology, according to the SWOT analysis. Indonesia can take these actions to capitalize on existing opportunities and make a greater contribution to the region's economy.